SST reconstruction from sediment cores M125-55-7/8 - Alicia Meng Xiao Hou; André Bahr; Stefan Schmidt; Cornelia Strebl; Ana Luiza Spadano Albuquerque; Cristiano Mazur Chiessi; Oliver Friedrich (PANGAEA, 2019)
The western tropical Atlantic (WTA) supplies warm and saline waters to the upper-limb of the Atlantic Meridional Overturning Circulation (AMOC) and may store excess heat and salinity during periods of AMOC slowdown. Since previous sea surface temperature (SST) reconstructions from the WTA typically focus on the Last Glacial Maximum and the last deglaciation, additional long-term records spanning several glacial-interglacial transitions are needed in order to elucidate the drivers of long-term WTA SST variability. We performed stable isotope and Mg/Ca analyses on the surface-dwelling planktonic foraminifera Globigerinoides ruber(pink) on a sediment core from the southern WTA to reconstruct surface-ocean changes over the past 322 kyr. We evaluate the relative importance of atmospheric pCO2 concentration, AMOC strength, and trade-wind intensity in driving the thermal evolution of the WTA across multiple glacial-interglacial cycles. Our SST record indicates that CO2 is the primary driver of glacial-interglacial SST variations in the southern WTA, however, its influence was strongly diminished during Marine Isotope Stage 6. A relatively stable cross-equatorial heat distribution over the past 322 kyr suggests that glacial-interglacial variations in AMOC strength did not drive past WTA SST changes at these timescales. The zonal SST contrast within the (sub)tropical South Atlantic displayed a clear glacial-interglacial mode of variability, which we attribute to low-frequency fluctuations in the strength of the southeast trade winds. Based on these findings, we hypothesize that increasing the concentration of greenhouse gases derived from anthropogenic activities may cause the southern WTA to become warmer and thermally homogenous, which may subsequently impact continental moisture-availability over tropical South America.
Supplement to: Hou, AMX et al. (2020): Forcing of western tropical South Atlantic sea surface temperature across three glacial-interglacial cycles. Global and Planetary Change, 188, 103150, https://doi.org/10.1016/j.gloplacha.2020.103150